(untitled) (Journal of Environment Sciences, 2025)
Nepal hosts over 923,000 registered businesses, with approximately 90% classified as Micro, Small, and Medium Enterprises (MSMEs). These businesses contribute to 45% of national employment, making them vital to economy. However, MSMEs face a significant financing gap, and climate change poses severe risks, particularly in sectors such as Non-Timber Forest Products (NTFPs), tourism, and aquaculture. The National Economic Census (2018) reports that climate change contributes to 1.8% of businesses failing to meet market demand, while 1.5% operate below full capacity due to climate-related factors. This study assesses MSME awareness of climate change, challenges, and impacts on production, costs, and raw material supply. Data were collected from 482 respondents across 16 districts in September 2024, revealed that most MSMEs are aware of climate change, yet struggle to adapt due to financial and resource constraints. Although awareness did not significantly differ between genders, a statistically significant difference was observed across age-groups. Key challenges include unpredictable weather patterns, increased pests and diseases, and declining raw material availability. The findings underscore the urgent need for targeted support to help MSMEs adapt to climate change. Policy recommendations include expanding access to climate finance, implementing capacity-building initiatives, and promoting market diversification strategies to enhance MSME resilience.